Analysis of nanocellular foaming with nucleating agents based on coarse-grained molecular dynamics simulations. (21st July 2022) - Morita, Hiroshi; Yoda, Satoshi; Ono, Takumi; Tazumi, Kouhei; Furuya, Takeshi
Abstract: Nanoscale foaming using nucleating agents was modeled based on coarse-grained molecular dynamics simulations to analyze the nucleation and growth of nanocellular foams. Interactions between the polymer chains and nucleating agents, the blowing rate, and the number of nucleating agents were varied, and foam formation was analyzed. Snapshots of the simulated foamed structures were obtained and characteristic parameters—such as the number of foams and the size distribution of the foams—were estimated. In the case of weak attractive interactions between the polymers and nucleating agents, foams formed first at the interfaces of the polymers and nucleating agents, then formed in the polymer matrix. In the case of strong attractive interactions, foams originated only in the polymer matrix. These nucleation-type foams depended on the number and size of the foams, and on their growth and coalescence. Our simulations indicate that the foamed structures can be modulated by the following parameters: interactions between the polymer chains and nucleating agents, the blowing rate, and the number of nucleating agents. Graphical abstract: Image 1 Highlights: Nanocellular foaming with nucleating agents was simulated using coarse-grained model. Nucleation, growth, and coalescence of nano foams can be reproduced by simulations. Foaming mechanism was changed by interactions between polymers and nucleating agents. There are two mechanisms: Foaming from nucleating agents and foaming within matrix.